BSD City Community Awareness Assessment About the Smart Building Concept - Taufik Trisandy Zakaria; Yuhana Astuti (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
An increase in the rate of population growth in urban areas needs development to facilitate community activities. This triggered the massive construction of high-rise buildings in various cities. With the construction of massive high-rise buildings usually do not see the impact on the environment. High-rise buildings usually consume a lot of energy and trigger gas emissions. In this case, smart building can be a solution to overcome the problem of energy inefficiency. The adoption of smart building also needs awareness from the community and the promotion of various synergies such as government, construction professionals. This study aims to determine the existence of a positive and significant influence on the organizational context, environment, and individual on the level of awareness of smart building The research method used in BSD City public awareness assessment research on the concept of smart building is to use quantitative methods with the aim of inferential research, the involvement of researchers no data intervention and data collection methods with cross sectional. The sampling technique used Yamane formula to determine the number of samples as many as 400 people. The results of this study show that there is a positive and significant influence of organizational context, environment and individual on smart building awareness. Based on the results of the study states that a significant key factor is in the process of making regulations and managerial to help increase awareness of smart building.